STUDY ON CLINICO-ETIOLOGICAL CORELATION AND OUTCOME OF VIRAL MENINGOENCEPHALITIS IN PEDIATRIC AGE GROUP IN A TERTIARY CARE CENTRE - Das, Leena; Murmu, Mangal Charan; Jena, Bijaylaxmi (International Journal of Research -GRANTHAALAYAH, 2018)
Meningoencephalitis remains the most significant cause of childhood deaths indeed a more measure cause of long term neurological handicap in children. Herpes simplex virus (HSV) encephalitis is recognized worldwide as the most frequent infectious encephalitis and the only one with a validated specific treatment. The incidence of viral encephalitis is 3.5-7.4 per 100,000 people per year. Aim & objectives: To study the demographic profile, etiological agent, clinical presentation, investigation findings and outcome of viral mengigoencephalitis in children. Material & Methods: The study was conducted in the pediatric department of SCB Medical College, Cuttack Odisha. Result: Highest incidence was observed in 1-5 years age group followed by 6-14 years. Males are more affected than Female. Highest number of cases occurred in summer season (45.2%). The common symptoms were fever (97.6%), irritability (80.9%), refusal to feed (80.9%), vomiting (80.9%), altered sensorium (76.1%), headache (61.9%), convulsion (52.3%). The common signs observed were temperature > 100.4̊ F (94.1%), meningeal sign (52.3%), GCS (Glasgow Coma Score) < 7 (52.3%), hypotension (50%), focal neurological deficit (52%).Viral marker were detected in 47.7% of cases. HSV (Herpes Simplex Virus) was common agent found among the positive viral marker detected. Conclusion: Viral mengingoencephalitis is a major health problem due to high morbidity and mortality. Early diagnosis is often difficult due to low incidence of disease specific signs. Detection of viral antibody is done by cerebrospinal fluid (CSF) Ig M & Ig G. PCR(Polymerase Chain Reaction) method is suggested as a better option which has more sensitivity and specificity and gives a rapid diagnosis.